Upaya Meningkatkan Kemampuan Teknik Passing Bawah dalam Permainan Bola Voli melalui Penerapan Metode Pembelajaran Kooperatif Students Team Achievement Divisions (STAD) Kelas X TKJ 3 SMK Negeri 2 Baubau Tahun Pelajaran 2018/2019 - Siti Marlina (Jurnal Akademik FKIP Unidayan, 2020)
This study to determine whether through cooperative learning Student Teams Achievement Divisions (STAD) methods can improve the capability technique of forearm pass the game of volleyball. The method used to answer the purpose of research methods the study used class-room action research or action research. The subjects were students of SMK Negeri 2 Baubau X TKJ 3 class totaling 32 students, including 25 boys and 7 girls. The results suggest the application of cooperative learning methods Student Teams Achievement Divisions ( STAD ) can increase the average activity score of teachers and students, the observation of students forearm pass technique and skills student to forearm pass. Cycle I mean teacher activity score of 6.5, the criteria to be increased in Cycle II with an average of 10 , criteria very well. Activities students first cycle an average score of 6.5, the criteria to be increased in Cycle II to 9.5, both criteria. Average scores below passing observation technique has increased, I cycle an average score of 9.25 observations, sufficient criteria, increases in Cycle II to 13.53, both criteria. For the values of students forearm pass, the first cycle by girls with an average number of 51.42, enough criteria, and boys student 52.80, sufficient criteria. In Cycle II score below passing skills increased, for by girls with an average 65.71, both criteria, and the boys student of 67.80, both criteria.